Balancing Monumentality and Everyday Life; The Modern Renovation of Stora Saluhallen - Li, Hao (My University, 2026)
This thesis focuses on Stora Saluhallen, an important historic heritage building in the city center of Gothenburg, and aims to explore how historically valuable buildings with strong everyday functional use can achieve a balance and mutually reinforcing relationship between everyday functionality and monumentality within a contemporary urban context. It should be noted that Stora Saluhallen underwent a renovation in 2012. Therefore, this study does not propose an implementable design intervention for the building itself, but instead uses it as a case study to present a broader approach to the adaptive reuse of similar spaces. The research also references on the renovation of many similar historical architectural spaces. Examples include Grand Palais and Musée d'Orsay in Paris. These buildings share common characteristics such as large and spacious vaulted structures and belong to a similar historical period. By examining these precedents, the study analyzes strategies for preserving and enhancing both the historical significance and the practical use value of Stora Saluhallen. Through field observation, architectural and spatial analysis, literature review, and contemporary case studies, the thesis systematically examines the market’s historical development, spatial organization, and patterns of use. On this basis, a theoretical framework and design foundation are established as a starting point for exploring methods to achieve the design objectives. The outcomes of the research include: Strategic recommendations for the modern renovation of historic market buildings; Comparative technical drawings and visualizations showing conditions before and after renovation;The production of design models and analytical diagrams. These outcomes aim to provide references for the sustainable use and cultural continuity of historic architecture within contemporary urban contexts.